The Textural Motif of Foliated Calcite in Ostreoidea (Mollusca) - Erika Griesshaber; Anna Sancho Vaquer; Antonio G. Checa; Carmen Salas; Elizabeth M. Harper; Wolfgang W. Schmahl (Crystals)
The microstructure of bivalve foliated calcite is extraordinary. It consists of units formed of stacks of folia with individual folia consisting of arrowhead-ended crystal laths. We investigated the texture of the foliated microstructure, the texture of individual and arrays of folia and the texture of assemblies of foliated units of the gryphaeid oyster Hyotissa hyotis with low kV, high-resolution, electron backscatter diffraction (EBSD). We base our understanding of the foliated texture on the combined interpretation of crystallographic aspects of individual and stacks of folia with the nature of crystal organization in a folium, a foliated unit and in foliated unit aggregations. Calcite c- and a*-axes arrangement in a folium is single-crystal-like. Due to the parallel organization of adjacent laths in a folium and the stacked arrangement of folia in a foliated unit, the assembly of calcite c- and a*-axes in foliated units is graded. The result is a ring-like distribution of c- and a*-axes orientations in the pole figures; nonetheless, the orientation rings are substructured by c- and a*-axes orientation clusters. The direction of the arrowhead endings of the laths is coincident with the growth direction of the shell. The morphology of arrowheaded laths initiates the formation of planes with {105}, {106} directions and a parallel orientation to the inner shell surface. H. hyotis’s foliated microstructure has a specific texture that is not fully understood. We discuss axial, spherulitic, turbostratic-like textures the foliated microstructure and suggest that the foliated texture of H. hyotis can, to some degree, be described with a turbostratic pattern.